Calcitonin receptor antibody validation and expression in the rodent brain. (August 2022) - Hendrikse, Erica R; Rees, Tayla A; Tasma, Zoe; Le Foll, Christelle; Lutz, Thomas A; Siow, Andrew; Wookey, Peter J; Walker, Christopher S; Hay, Debbie L
Background and aim: Therapeutics that reduce calcitonin gene-related peptide activity are effective migraine treatments. However, gaps remain in our understanding of the molecular mechanisms that link calcitonin gene-related peptide to migraine. The amylin 1 receptor responds potently to calcitonin gene-related peptide, and to the related peptide amylin, but its role in relation to either peptide or to migraine is unclear. We sought to better understand the expression of the amylin 1 receptor protein subunit, the calcitonin receptor, in the rodent brain. Methods: We profiled three antibodies for immunodetection of calcitonin receptor, using immunocytochemistry, western blotting, and calcitonin receptor conditional knockout mouse tissue. Selected migraine-relevant rat brain regions were then examined for calcitonin receptor-like immunoreactivity. Results: All three antibodies detected calcitonin receptor protein but only one (188/10) produced robust immunostaining in rodent brain, under the conditions used. Calcitonin receptor-like immunoreactivity was apparent in the rat brainstem and midbrain including the locus coeruleus, periaqueductal grey and spinal trigeminal nucleus. Conclusions: Anti-calcitonin receptor antibodies require comprehensive profiling to ensure confidence in the detection of calcitonin receptor. Using a validated antibody, calcitonin receptor-like immunoreactivity was detected in several brain regions relevant to migraine. Further research is needed to understand the functional consequences of calcitonin receptor expression for calcitonin gene-related peptide or amylin physiology and pathophysiology.